Percutaneous Placement and Management of Peritoneovenous Shunts - Martin, Louis G. (Seminars in Interventional Radiology, 2012)
Peritoneovenous shunts are used in the treatment of recurrent ascites or recurrent pleural effusions. Generally speaking, the shunts allow passage of ascites or pleural effusions (by either passive or active means) back into the central venous system. The most recent development in peritoneovenous shunts, known as the Denver Shunt, is a modification of a shunt developed for the treatment of hydrocephalus. In recent years, the Denver shunt has been placed by interventional radiologists. It is used to treat both cirrhotic and malignant effusions in the peritoneal and pleural cavities. Reported complications of the shunt are shunt occlusion, infection, post-shunt coagulopathy, deep vein thrombosis, catheter breakage, and leaks. This article discusses the technical aspects related to the percutaneous placement and maintenance of the Denver Shunt.
Keywords: ascites; pleural effusion; catheter drainage; shunts; interventional radiology